2019
DOI: 10.1080/08964289.2018.1541862
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Psychosocial Intervention on Positive Affect and Posttraumatic Growth for Chinese American Breast Cancer Survivors: A Pilot Study

Abstract: Breast cancer survivors report persistent psychological and physical symptoms, which affect their quality of life and may challenge the recovery process. Due to social, cultural, and linguistic barriers, culturally-sensitive care is largely unavailable for Chinese Americans, and their psychological needs are not often addressed. We aimed to investigate whether the Joy Luck Academy (JLA), a psychosocial intervention providing both information and peer support, was associated with positive adjustment among Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…Six interventions sought to improve quality of life (Chee et al, 2017; Deng et al, 2016, 2019; Lu et al, 2012, 2017, 2018). Two of the interventions intended to improve posttraumatic growth (Lu et al, 2012; Warmoth et al, 2020), which refers to individuals’ positive transformation after hardship and struggle (Tedeschi & Calhoun, 1996). Two interventions (Mokuau et al, 2008, 2012) sought to increase knowledge, self-efficacy, and coping among survivors and their family members.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six interventions sought to improve quality of life (Chee et al, 2017; Deng et al, 2016, 2019; Lu et al, 2012, 2017, 2018). Two of the interventions intended to improve posttraumatic growth (Lu et al, 2012; Warmoth et al, 2020), which refers to individuals’ positive transformation after hardship and struggle (Tedeschi & Calhoun, 1996). Two interventions (Mokuau et al, 2008, 2012) sought to increase knowledge, self-efficacy, and coping among survivors and their family members.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 5 out of the 13 interventions were from one research group (Lu and colleagues) and four from another research group (Im and colleagues). This predominance of these two teams of researchers Interactive online discussion board, online educational sessions, online resources Deng et al (2016) Support group meetings, educational seminars, one-on-one peer support, educational materials, newsletters Deng et al (2019) Personally tailored workbook for dietary behaviors; quarterly newsletters, consultation with registered dietitians, phone counseling and prompts Im et al (2019) A technology-based information and coaching/support program including educational modules, online resources, group and individual coping by nurse interventionists Online educational modules, online resources, and group and individual (one-to-one) coaching Lu et al (2012) Expressive writing Lu et al (2014) Peer mentoring and educational sessions Lu et al (2017) Expressive writing Expressive writing Mokuau et al (2008) Family-oriented intervention providing educational sessions Mokuau et al (2012) Family-oriented educational sessions Warmoth et al (2020) Intervention included an educational component and a peer-mentoring component suggests the need for training, developing, and supporting a greater number of investigators who can generate a greater diversity in theoretical perspectives and methodological approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a pilot study suggested that Joy Luck Academy has the potential to improve well-being among Chinese American breast cancer survivors [ 17 , 23 ]. Furthermore, qualitative data revealed that Joy Luck Academy reduced perceived stigma and loneliness and increased a sense of belonging by providing a forum for participants to share their experiences with women of similar cultural backgrounds [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTG has been found to exist in various populations after facing a traumatic event, including victims of the Oslo and 9/11 terror attacks [ 10 , 11 , 20 ] and mass violence [ 21 ], those with physical illnesses [ 9 , 21 , 22 , 23 , 24 ], sexual abuse victims [ 8 ], college students experiencing trauma [ 14 , 15 , 25 ], and veterans [ 26 ]. A higher level of PTG is generally associated with greater trauma and those who struggle with trauma are more likely to experience PTG [ 13 ].…”
Section: Introductionmentioning
confidence: 99%